Climate change : What Everyone Needs to Know - Romm, Joseph J. (What everyone needs to know., 2018)
"The essential primer on what will be the defining issue of our time, Climate Change: What Everyone Needs to Know® is a clear-eyed overview of the science, conflicts, and implications of our warming planet. From Joseph Romm, Chief Science Advisor for National Geographic's Years of Living Dangerously series and one of Rolling Stone's "100 people who are changing America," Climate Change offers user-friendly, scientifically rigorous answers to the most difficult (and commonly politicized) questions surrounding what climatologist Lonnie Thompson has deemed "a clear and present danger to civilization." New questions about climate change addressed in this guide include:· Analysis of the Paris climate agreement, including the United States' withdrawal - Examines implications of the clean energy revolution, from solar and wind power to batteries and electric cars - The latest on climate science, including updates on efforts to stem or slow climate change - Insights into what Donald Trump's presidency means for climate action in the US and internationally. As the global response to climate change continues to evolve, Climate Change: What Everyone Needs to Know® offers smart, unbiased answers to the most difficult questions in an area dogged by misunderstanding and politicization."--Provided by publisher